2016
DOI: 10.1186/s12936-016-1585-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to the full-length VAR2CSA and its DBL domains in Cameroonian children and teenagers

Abstract: BackgroundAntigenic variation of Plasmodium falciparum erythrocyte membrane protein 1 is a key parasite mechanism for immune evasion and parasite survival. It is assumed that the number of parasites expressing the same var gene must reach high enough numbers before the host can produce detectable levels of antibodies (Ab) to the variant. VAR2CSA is a protein coded for by one of 60 var genes that is expressed on the surface of infected erythrocytes (IE) and mediates IE binding to the placenta. The idea that Ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This is also evident from the finding of only P. falciparum as the cause of clinical malaria in the target population. In this study, the levels of all the IgG subclasses increased with age overall, which corroborates the findings of other studies performed in Cameroon [39, 40]. This could be attributed to the increasing number of exposure to malaria parasite infection with age.…”
Section: Discussionsupporting
confidence: 92%
“…This is also evident from the finding of only P. falciparum as the cause of clinical malaria in the target population. In this study, the levels of all the IgG subclasses increased with age overall, which corroborates the findings of other studies performed in Cameroon [39, 40]. This could be attributed to the increasing number of exposure to malaria parasite infection with age.…”
Section: Discussionsupporting
confidence: 92%
“…Field studies have previously reported low levels of anti-VAR2CSA antibodies in children, men and teenage girls. [25][26][27] Therefore, antibodies to VAR2CSA seems to be acquired, to some extent, outside of the pregnancy context. This could be the consequence of prior exposure to VAR2CSA or to malaria antigens sharing common epitopes with VAR2CSA such as other PfEMP1 or P. vivax Duffy Binding Protein (PvDBP).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 338 AE and 186 adverse events following immunization (AEFI) related to the vaccine were documented (Table 2 and Table S3; appendix pp 12-13). For the cohort A (n=6), 54 AE were reported, 45 related to the vaccine: 25 Table 3).…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…The expression of VAR2CSA is generally assumed to be incompatible with parasite survival in nonpregnant individuals ( 6 , 8 ). Therefore, the acquisition of VAR2CSA-specific IgG is normally regarded as being pregnancy restricted, despite a few reports of sporadic, low levels of VAR2CSA-specific IgG among P. falciparum -exposed men, children, and nulligravidae ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%